Nilai Ekonomis Produksi Tempe di Desa Padaringan Kec. Purwadadi Kab. Ciamis Jawa Barat - Arif Nugroho Wibowo; Zainal Arifin; Bambang Perkasa Alam; Nini Adelina Tanamal (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the economic value of small-scale household tempe agroindustry in Padaringan Village, Purwadadi District, Ciamis Regency. The research employed a quantitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation of tempe producers, and analyzed using cost, revenue, income, business efficiency (R/C ratio), and value-added analysis based on the Hayami method. The results show that the total production cost per cycle was IDR 333,000, while total revenue reached IDR 1,530,000, generating an income of IDR 1,197,000. The R/C ratio of 4.59 indicates that the tempe business is highly efficient and economically feasible. Value-added analysis reveals a high added value ratio of 78.23%, indicating that most of the product’s value is generated from processing activities. These findings demonstrate that the tempe agroindustry plays an important role in increasing household income and strengthening the local economy. The tempe industry has strong potential to be developed as a leading sector in rural economic empowerment through improved production efficiency, product innovation, and strengthened marketing networks.